Kidney Stones Are Prevalent in Individuals with Pseudoxanthoma Elasticum, a Genetic Ectopic Mineralization Disorder - Douglas Ralph; Rina Allawh; Ian F. Terry; Sharon F. Terry; Jouni Uitto; Qiao-Li Li (Wolters Kluwer Health, 2020)
Abstract. Objective:. Pseudoxanthoma elasticum (PXE) is a rare genetic disorder caused by loss-of-function mutations in the ABCC6 gene. While PXE is characterized by ectopic mineralization of connective tissues clinically affecting the skin, eyes, and cardiovascular system, kidney stones were reported in some individuals with PXE. The aim of this study is to determine whether kidney stones are an incidental finding or a frequent manifestation of PXE. Methods:. We first investigated the genetic basis of two siblings diagnosed with PXE. The younger patient presented with recurrent kidney stones since 8 years old. Secondly, to address whether kidney stones are associated with PXE, the prevalence of kidney stones in a survey cohort of 563 respondents with PXE was compared to that of a general U.S. population survey, National Health and Nutrition Examination Survey, with 28,629 participants. Results:. Genetic analysis in both patients identified compound heterozygous mutations in ABCC6, c.2787+1G>T, and c.3774_3775insC. The analysis of participants 20 years old and older revealed that 23.4% of PXE patients had previously had a kidney stone, a significant increase compared to 9.2% in the general population (P < 0.01). In addition, 17.8% of PXE patients reported their first kidney stone episode before age of 18 years old. Conclusions:. PXE correlates with an increased risk of developing kidney stones with considerable morbidity and health-care cost.